An Analysis of Translation Quality and Challenges Faced by English Student of UNP in Translating English-Indonesian Onomatopoeia - Syukrina, Dinda; Oktavia, Witri (Journal of English Language Teaching, 2025)
This study aims to analyze the translation quality and challenges faced by English Department students at Universitas Negeri Padang (UNP) in translating onomatopoeia from English into Indonesian. The research focuses on two key aspects of translation quality: accuracy and acceptability, as well as the common challenges encountered during the translation process. A descriptive qualitative method was used, employing a translation test and a questionnaire as instruments, with 24 students from the 2022 Translation class serving as participants. The findings show that the students' translations were generally categorized as almost accurate and almost acceptable. The study also revealed several key challenges, including subjectivity in interpretation, phonological differences, and differences in register and style between the source and target languages. These results suggest that translating onomatopoeia requires not only linguistic competence but also cultural awareness and creative strategy use. The study is expected to contribute to improving translation pedagogy and serve as a reference for future research focusing on translation strategies for onomatopoeia.